DBA's guide to databases on Linux - Rogers, Chris; Syngress Media, Inc. (Rockland, MA : Syngress Media : Distributed by Publishers Group West, 2000)
In an effort to increase its marketshare and threat to Windows NT, Oracle8 was ported to Linux in late 1998, opening the popular database to an additional 10 million Linux users worldwide. The availability of Oracle8 enables current Linux users to deploy enterprise-class applications at low cost and provides an alternative to Microsoft Windows NT. This book covers that marriage of the most popular database and the fastest growing operating system. * Complete coverage. Covers both Oracle8i and Oracle8i Lite, as well as Oracle Applications, Oracle Applications Server, and Oracle Developer * Organizations and Oracle database administrators will be looking for information on Linux as is gets adopted - this book fits the bill * Covers two growth markets and fills a need for information not covered elsewhere.
Includes index.
Keywords: Linux; Oracle (Computer file); Database management; MySQL (Computer file); Electronic books